2017
DOI: 10.1155/2017/1659176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Operational Effects of Bus Lane with Intermittent Priority under Connected Vehicle Environments

Abstract: Bus lane with intermittent priority (BLIP) is an innovative method to improve the reliability of bus services while promoting efficient usage of road resources. Vehicle-to-vehicle (V2V) communication is an advanced technology that can greatly enhance the vehicle mobility, improve traffic safety, and alleviate traffic jams. To explore the benefits of BLIP operation under a connected environment, this study proposed a three-lane cellular automata (CA) model under opening boundary condition. In particular, a mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…In a connected vehicle environment, existing studies have explored the implementation of forced lane change rules underlying the CV-based BLIP strategy. A microsimulation analysis shows CV-based BLIP could result in up to 32% benefit compared with a dedicated bus lane [3,10] in arterial. Recommended clear distance is between 300 and 500 meters.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a connected vehicle environment, existing studies have explored the implementation of forced lane change rules underlying the CV-based BLIP strategy. A microsimulation analysis shows CV-based BLIP could result in up to 32% benefit compared with a dedicated bus lane [3,10] in arterial. Recommended clear distance is between 300 and 500 meters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e original BLIP concept was based on road segments and used variable message signs (VMSs) to provide information on vehicle rights-of-way. e road network geometry and intersection locations determine the length of each road segment [3][4][5][6]. If a bus is detected to be moving in the lane, the road segment of BLIP will continue to change to a bus lane one by one.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the HCM2010 vehicle delay formula and road resistance function, a model of the average and per capita travel time of vehicles under different road conditions was established, and the setting conditions of the bus lane were given; Qiufeng and Wenquan [4] analyzed the variation of the total delay error of the intersection before and after the intermittent bus entrance lane was set up and found that when the traffic saturation of the entrance lane is less than the critical traffic saturation, the delay in setting the intermittent bus-dedicated entry lane is lower; in exploring the capacity in terms of influencing factors, Yulin et al [5] improved the space utilization rate by dynamically controlling the opening time of intermittent bus entrance lanes to social vehicles and conducted a quantitative analysis of social vehicle delays at intersections; Dingxin [6] introduced the anticollision rule which puts forward the capacity reduction mechanism of intermittent priority bus lanes and concluded that the increase in clearing distance and the decrease of the bus departure interval will reduce the capacity of intermittent priority bus lanes; Eichler and Daganzo [7] used the theory of distributed waves. e analysis found that social traffic saturation and bus departure frequency are the key factors that affect the effectiveness of intermittent bus lanes; Wu et al [8] formulated mandatory intermittent bus lane-changing rules in a vehicle-route coordination environment. e simulation model was used to analyze the control effect under different departure time intervals and vehicle density; Qiu [9] and others analyzed the impact of the IBL on the traffic density, speed, and flow of the road section through computer simulation, indicating that the service level is the turning point for the implementation of the IBL strategy; Wu et al [10] proposed a method to provide intermittent priority for dedicated bus lanes and analyzed the influence of departure frequency on delays; in terms of signal correlation control, Guler et al [11] proposed a similar advance signal control strategy of intermittent bus lanes which is to install auxiliary signal lights in the upstream and downstream of the main line signal to control the operation mode of the bus; Ma and Xu [12] proposed a bus priority strategy and gave a green wave coordination control method for the bus operation line; Chiabaut and Barcet [13] evaluated the impact of the intermittent bus lane strategy on traffic conditions and pointed out that the travel time of buses will be significantly reduced when combined with bus signals.…”
Section: Introductionmentioning
confidence: 99%
“…e managed lane strategy can improve traffic conditions by setting up dedicated lanes for specific vehicles. Bus lanes, high-occupancy vehicle (HOV) lanes, and high-occupancy toll (HOT) lanes are all based on similar concepts and have proven their feasibility through practices [34][35][36]. Due to the limitations of technologies, studies on the CAV dedicated lane are still at the theoretical level and have not been put into practice.…”
Section: Introductionmentioning
confidence: 99%